Reflecting on the Strength of Observable Curricular Reality of an Alternative School: from the Lens of ΝΕΡ 2020 - Mehta, Sonam; Yadava, Shalini (Voices of Teachers and Teacher Educators, 2023)
The National Education Policy 2020 has brought in new horizons, new guidelines, fresh perspectives and newer aspirations for all the stakeholders in the field of education. The new policy perspective emphasises on ensuring an honest attempt, towards providing such educational environment to our children, that it facilitates their innate holistic development. On these guiding principles, the curriculum framers, educational administrators and the teachers working at the grass-root level, are thinking, how they can redesign, innovate and progressively transform their teaching-learning environments, pedagogic processes, to make these principles a living reality. In such a period of curricular transformations, looking at the best practices and curricular working models, which work on the same principles of individualized curriculum plans, natural learning, skill-based education, value inculcation and letting the child prosper in his own way to reach the zenith zenith of his individual excellence, is significant for contemporary research in curriculum construction and development. This paper presents a reflective analysis on a series of classroom observations and interactions with teachers done in an alternative school of Delhi known as Mirambika’. This school works on the educational philosophy and vision of ’Sri Aurobindo’ and his spiritual associate The Mother’. This alternative form of education is known as ’Integral Education’, This paper includes anecdotal records of a day spent in this school and an account of how their teaching-learning ethos, made the researcher reflect continuously on how in a way, the principles mentioned in NEP are unfolding before her in actual action. The first attempt of this paper is to bring forth a potential curriculum model for study, which can bring us useful inputs for re-structuring our main school formalized curriculum, to facilitate the shift desired in NEP 2020. The second attempt of the paper is to reflect on the richness of the educational ideologies of the alternative schools in India which have been since long struggling to survive in the vicinity of expansive formalized schooling. The principles of non-flexibility, stringent syllabus, rigorous examination system and expansive syllabus, that have always been considered the hallmarks of education standards of formal education, are no more the celebrated concepts in contemporary times. This paper brings in newer reflections on the contemporary significance of the educational principles of alternative form of schooling. The ’observable in practice principles of Alternative schooling’ namely flexibility, non-stringent syllabus, non-formalized assessment, non- formal learning environment, focus on the joy of learning through discovery and reflective individualized curriculum plans, are now the aimed objectives of the contemporary curriculum framers after NEP, thus, making the alternative schools a rich curricular model for educational research in present times.